Pelaksanaan Penerimaan Peserta Didik Baru Sistem Zonasi di SMA Negeri 13 Palembang - Setyaningsih, Kris; Meidiani, Annisa; Ibrahim, Ibrahim; Fatmawaty, Fatmawaty (Indo-MathEdu Intellectuals Journal, 2024)
This study aims to analyze the implementation of the zonation system for new student admissions at SMA Negeri 13 Palembang. The research adopts a qualitative approach with a descriptive research design. Data collection techniques include observation, interviews, and documentation. Data analysis techniques used are data reduction, data presentation, data verification, and conclusion drawing. The validity of the data in this research was ensured through source triangulation and technique triangulation. The results of the study indicate that the implementation of the zonation system for new student admissions at SMA Negeri 13 Palembang has been carried out effectively. This can be observed through the execution of several key indicators in the new student admission process, including analyzing student needs, registering prospective students, selecting students, determining accepted students, and re-registration. The overall process of implementing the zonation system for new student admissions has been well-organized and effectively managed